Identifying features in the structural and phase composition of the products of recycling of the scale of high-speed cutting steel by carbon thermal reduction - Borysov, Viacheslav; Torubara, Oleksii; Volokh, Vadym; Poliakov, Anatolii; Yamshinskij, Mykhail; Lukianenko, Ivan; Andreev, Andrey; Bilko, Tamara; Zhuravel, Dmytro; Ivanchenko, Dmytro (Eastern-European Journal of Enterprise Technologies, 2022)
This paper reports a study into the features of the structural-phase composition of products from the carbon-thermal reduction of scale of high-speed steels that yields an alloying additive. This is necessary to determine the technological parameters that reduce the loss of target elements in the process of obtaining and using resource-saving alloying material. The study indicates that when the degree of scale reduction changed from 28 % to 67 % and 81 %, an increase in the manifestation of a solid solution of carbon and alloying elements in the α-Fe lattice was observed. At the same time, the intensity of the diffraction maxima of FeO and Fe3O4 decreased. In the reduced products, the presence of Fe3C, FeW3C, Fe3W3C, and WC was traced. With an increase in the degree of scale reduction from 28 % to 67 %, the disordered (of "loose" appearance) microstructure was replaced with the formed particles of round and multifaceted shape with different content of alloying elements. At the reduction stage of 81 %, the microstructure had a finely fibrous structure. Based on the suite of studies, the most acceptable degree of reduction of scale of high-speed steel, followed by the use of the obtained material as an alloying additive, is 81 %. At the same time, ensuring the degree of recovery at the level of 67 % would also suffice. This is due to the fact that residual carbon in the form of carbides provides an increased reducing ability and degree of assimilation of alloying elements with the restoration of the residual oxide component in the liquid metal during doping. Spongy microstructure contributes to faster dissolution, in relation to the corresponding standard ferroalloys. This ensures a reduction in the total smelting time and, as a result, a decrease in the energy consumed